Theoretical Foundations for Modelling Bedside Rounds as a Teaching and Practice Activity (I) - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Medisur)
Bedside rounds are one of the most important teaching organizational forms in medical training at every level. In this paper, three basic ideas for shaping such rounds are presented: their condition of human activity, their practice essence as well as their formative purpose. In addition, the first two ideas are developed. Concrete implications of these ideas in the creation of a representation or form for bedside rounds are specified.